2009
DOI: 10.1093/hmg/ddp389
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in COG5 causes a moderate form of congenital disorders of glycosylation

Abstract: The conserved oligomeric Golgi (COG) complex is a tethering factor composed of eight subunits that is involved in the retrograde transport of intra-Golgi components. Deficient biosynthesis of COG subunits leads to alterations of protein trafficking along the secretory pathway and thereby to severe diseases in humans. Since the COG complex affects the localization of several Golgi glycosyltransferase enzymes, COG deficiency also leads to defective protein glycosylation, thereby explaining the classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 32 publications
5
81
0
1
Order By: Relevance
“…Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006;Foulquier et al, 2007;Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) suggesting a role for COG in the retention and/or retrieval of Golgi glycosylation enzymes. Indeed, loss of COG subunits impaired the localisation and the stability of Golgi resident proteins, which are known to recycle within the Golgi stacks (Oka et al, 2004;Zolov and Lupashin, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006;Foulquier et al, 2007;Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) suggesting a role for COG in the retention and/or retrieval of Golgi glycosylation enzymes. Indeed, loss of COG subunits impaired the localisation and the stability of Golgi resident proteins, which are known to recycle within the Golgi stacks (Oka et al, 2004;Zolov and Lupashin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, subunits of Lobe A are essential components of the complex (VanRheenen et al, 1998;Whyte and Munro, 2001;Wuestehube et al, 1996), whereas Lobe B subunits are not substantially required for cell growth or internal membrane organisation (Ram et al, 2002;Whyte and Munro, 2001). Mutations in the genes encoding human COG1, COG4-COG8 have been associated with congenital disorders of glycosylation (CDG) (Foulquier et al, 2006Foulquier et al, 2007Kranz et al, 2007;Lübbehusen et al, 2010;Ng et al, 2007;Paesold-Burda et al, 2009;Reynders et al, 2009;Spaapen et al, 2005;Steet and Kornfeld, 2006;Wu et al, 2004) indicating a role for COG in the transport and/or stability of Golgi glycosylation enzymes. Indeed studies in both yeast and mammalian cells have suggested that COG complex might function as a vesicle-tethering factor in intra-Golgi retrograde COPI transport (Ungar et al, 2002), thus regulating the distribution and the stability of Golgi resident proteins (Oka et al, 2004;Shestakova et al, 2006;Suvorova et al, 2001;Suvorova et al, 2002;Walter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, COG5 mutations were reported in several CDG patients (24,25,39); substantial clinical overlap between COG5-CDG and COG7-CDG was noted (25). Most of the known COG5-CDG patients carry homozygous nonsense or exon skipping mutations (25,39).…”
Section: Significancementioning
confidence: 99%
“…Most of the known COG5-CDG patients carry homozygous nonsense or exon skipping mutations (25,39). Potentially more informative, from a COG structural standpoint, is a patient with relatively mild symptoms and different mutations in her maternal and paternal copies of the COG5 gene (24,25).…”
Section: Significancementioning
confidence: 99%
“…The identification of milder cases of COG6 and COG7 deficiency harboring different mutations [56,57] however shows that the severity of the disease does not simply relate to the subunit affected but rather to the capability of forming a fully functional COG complex. Besides the severe diseases observed for COG6 and COG7 defects, moderate clinical manifestations have been associated with mutations in COG1 [58,59], COG2 [60], COG4 [61,62], and COG5 [63][64][65].…”
Section: Localization Of Glycosyltransferasesmentioning
confidence: 99%